ANALYSIS OF ROAD TRAFFIC INJURIES ON PUBLIC TRANSPORT IN THE REPUBLIC OF TATARSTAN OVER THE YEARS 2018-2022 - TIMERZYANOV, MARAT I.; DELYAN, ARTUR M.; KHAIRUTDINOV, NAIL N.; SHARAFUTDINOVA, ADELIYA R. (The Bulletin of Contemporary Clinical Medicine, 2023)
Report. Introduction. Road traffic accidents involving passenger transport vehicles are characterized by highly severe consequences and usually cause massive public outcry. Major accidents involving public transport occur infrequently, but they are always characterized by many victims, injured and dead. Aim of this paper is to study the injury degree of road traffic accidents involving passenger transport vehicles, such as buses, trolleybuses, or trams. Materials and Methods. The study is based on the data made available via the federal statistical observation over road accidents involving motor and public transport in the Republic of Tatarstan over the years 2018-2022. For this purpose, we used generalization methods and quantitative, qualitative, and comparative analysis techniques. Mathematical simulation techniques were used to analyze the data with the computational tools of the MS Excel electronic package. Необходимо повышение осведомленности пассажиров о правилах безопасности и процедурах эвакуации в случае чрезвычайного проис- шествия. Results and Discussion. An acute problem of modern society is the lack of effectively ensuring passenger transport safety, which leads to more frequent road accidents and injuries on the roads. Transporting passengers by urban public transport is one of the most important industries in the economy of the Republic of Tatarstan. Road safety issues are a priority in many strategic and program documents of the socio-economic development of the Republic. Human factor is one of the key factors in ensuring road safety. The most common causes of such accidents are speed limit violations and drivers’ inattention and negligence. Eventually, drivers’ failure to comply with the work-rest ratio leads to accidents and loss of life. There is a need for raising passengers’ awareness of safety rules and emergency evacuation procedures. Conclusions. There are still serious shortcomings in traffic management, leading to accidents with many dead and injured. Implementing measures aimed at preventing road accidents will help enhance road safety and significantly reduce the number of accidents.